2009
DOI: 10.1111/j.1365-2133.2009.09293.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated aldosterone levels in patients with androgenetic alopecia

Abstract: The elevated aldosterone values in these patients may contribute, together with other mechanisms, to the development of AGA and may also explain the higher prevalence of hypertension. Blood pressure screening of patients with AGA will permit earlier diagnosis of an unknown hypertension and initiation of appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 9 publications
2
16
0
1
Order By: Relevance
“…That study found significantly higher systolic BP values and aldosterone levels in alopecic vs. nonalopecic men; however, no differences in diastolic BP levels were found. 16 These results corroborate the second hypothesis, which is consistent with the development of alopecia in transgenic mice with cutaneous overexpression of mineralocorticoid receptors. 11 It is also supported by the present finding of higher aldosterone values in female patients with AGA and hypertension than in hypertensive controls.…”
Section: Discussionsupporting
confidence: 88%
“…That study found significantly higher systolic BP values and aldosterone levels in alopecic vs. nonalopecic men; however, no differences in diastolic BP levels were found. 16 These results corroborate the second hypothesis, which is consistent with the development of alopecia in transgenic mice with cutaneous overexpression of mineralocorticoid receptors. 11 It is also supported by the present finding of higher aldosterone values in female patients with AGA and hypertension than in hypertensive controls.…”
Section: Discussionsupporting
confidence: 88%
“…This study found significantly higher systolic BP values and aldosterone levels in patients with alopecia versus control subjects, therefore these results corroborate the second hypothesis, which is consistent with the development of alopecia in transgenic mice. 20,21 Sadighha and Zahed 22 recently confirmed that male patients with AGA have elevated triglyceride levels. Similar results were found by Matilainen et al 23 in a study of triglyceridemia in men who had undergone revascularization as a result of heart disease.…”
Section: Metabolic Syndromementioning
confidence: 82%
“…The pathogenetic mechanisms of atherosclerosis are quite well known, but the pathogenetic link between alopecia and atherosclerosis is not clear (12,13). Higher cholesterol-and trigyceride-levels participate along with other mechanisms initiating atheromatous plaque.…”
Section: Discussionmentioning
confidence: 98%